KOLABORASI GURU AGAMA ISLAM DENGAN GURU BAHASA DALAM MENINGKATKAN PRESTASI EKSTRAKURIKULER BIDANG KEAGAMAAN SISWA - Ali Jusri Pohan (Edu Global : Jurnal Pendidikan Islam, 2020)
The purpose of this study was to determine how the collaboration between Islamic religious teachers and language teachers in improving extracurricular achievements in the religious field of students at MAN 2 Padangsidimpuan. This type of research is field research (field research) with qualitative descriptive research methods. Data collection techniques include observation, interviews and documentation. PAI teachers teach students about religious material, Indonesian teachers teach students about grammar, Arabic and English teachers teach students to compile religious texts that are directly related to Arabic and English texts, and teach how to pronounce and intonate them. Supporting factors for collaboration between PAI teachers and language teachers, namely: solid cooperation between teachers in guiding students when there is a competition/MTQ, providing input and ideas to each other